Development of a network model to implement the HPV vaccination coverage - Guarducci, Giovanni; Chiti, Marinella; Fattore, Dimitri Carlo; Caldararo, Raffaele; Messina, Gabriele; Filidei, Paolo; Nante, Nicola (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. The vaccination coverage of a population is the usual indicator of the effectiveness of vaccination strategies. The study aims to evaluate the effectiveness of an organizational and communication network to implement Human Papilloma Virus (HPV) vaccination coverage both in males and females in the Center Tuscany Local Health Authority.Study design. Experimental study.Materials and methods. In January 2022, a retrospective study was conducted on anti-HPV vaccine coverage (full cycle), of those born from 2007 to 2010, in the Empoli Territorial Area of Florence (240 thousand inhabitants) under the Center Tuscany Local Health Authority. In February 2022, a project (meetings with general practitioners and pediatricians, communication through local media, increased opening hours of vaccination clinics and continuous monitoring of vaccination status) started to recover the females and males non-compliant; in the first five months, in addition to guaranteeing the offer to the reference cohort, it aimed to recover the 2007, 2008 and 2009 cohorts, while in the following six months the anti-HPV vaccine offer was expanded for the 2010 cohort.Results. In January 2022, for all cohorts the average total coverages were 49.2% (49.1% for females and 49.5% for males), while in December 2022 they were 63.9% (65.8% for females and 62.3% for males). Coverage increased by 15.6% (+14.2% for females and +16.8% for males) for the 2007 birth cohort, by 22.3% (+20.6% for females and +23.7% for males) for the 2008 cohort and by 20.9% (+31.4% for females and +10.6% for males) for the 2009 cohort.Conclusions. This model in force in the whole Center Tuscany Local Health Authority for a few years and already activated in the previous Local Health Authority of Empoli, now called Empoli Territorial Area, has allowed to implement the Human Papilloma Virus vaccine coverage for both genders.